Learning Media Through Balinese Songs (BaLe LaLi) to Improve Learning Outcomes in Civic Education for Fourth Grade Students - Dewi, Ni Putu Eka Vicky Aprilia; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Journal of Education Technology, 2025)
The low learning outcomes of students in the topic of rights and obligations in Civic Education indicate the need for innovative instructional media that can enhance student engagement and comprehension. The absence of culturally based, engaging media also poses a challenge in optimizing meaningful learning experiences. This study aims to develop, validate, and evaluate the effectiveness of an interactive learning media called BaLe LaLi (Belajar Lewat Lagu Bali), which integrates a traditional Balinese song into culture-based learning. This research employs a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects involved three experts (content, instructional design, and media), as well as 32 fourth-grade students divided into individual testing (3 students), small group testing (9 students), and field testing (20 students). Data were collected through observation, interviews, validation questionnaires, and learning achievement tests (pre-test and post-test), and analyzed using the paired sample t-test. The findings reveal that BaLe LaLi media is highly valid with an average score of 93.5%, and effectively improves student learning outcomes, with the mean score increasing from 68.5 in the pre-test to 86.59 in the post-test (t = 4.899; p < 0.05). Besides enhancing academic performance, this media is relevant for character building and preserving local culture through learning. The implications of this study suggest the potential for developing similar media integrating local culture to improve learning motivation and support character education in various educational themes.